Penerapan Model Explicit instruction untuk Meningkatkan Hasil dan Aktivitas Belajar Siswa Kelas X IPA 2 MAN 1 Pidie dalam Materi Stoikiometri - Nursiah, Nursiah (Jurnal Ilmiah Guru Madrasah, 2022)
Explicit instruction is a teaching approach that involves explaining material face-to-face, directly, gradually, and systematically, so that it helps students more easily learn and understand the material being taught. This is a classroom action research (CAR) study that aims to improve learning outcomes and student learning activities in the stoichiometry material chemistry learning process by implementing the explicit instruction model. This research was conducted in class X IPA 2 in semester 1 of the 2020–2021 academic year with a total of 24 students. This study consisted of two cycles, and each cycle consisted of two meetings with a duration of 90 minutes. The data in this study were obtained from the results of written tests at the end of the first and second cycles as well as the results of observations at each meeting by one teacher acting as an observer. The results of this study indicate that there was an increase in student learning outcomes in cycle I, with a complete percentage of 62.5% and an incomplete percentage of 37.5%. In the second cycle, there was an increase in student learning outcomes, with a complete percentage of 91.66% and an incomplete percentage of 8.34%. Student activity also increased from active to very active, with an average activeness percentage of 90.63%. This proves that learning activities using the explicit instruction model can improve student learning outcomes and are able to encourage student activity in the learning process. Thus, this study concluded that the application of the explicit instruction learning model to students using stoichiometric material was proven to be able to improve student learning outcomes and activities. Abstrak Explicit instruction merupakan sebuah pendekatan mengajar dengan menjelaskan materi secara tatap muka, langsung, bertahap dan sistematis sehingga membantu siswa agar lebih mudah mempelajari dan memahami materi yang sedang di ajarkan. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang berupaya untuk meningkatkan hasil belajar dan aktivitas belajar siswa dengan menerapkan model  explicit instruction dalam proses pembelajaran kimia materi Stoikiometri. Penelitian ini dilaksanakan di kelas X IPA 2 pada semester 1 tahun pembelajaran 2020/2021 dengan jumlah siswa sebanyak 24 orang. Penelitian ini terdiri dari dua siklus dan masing-masing siklus terdiri dari dua pertemuan dengan durasi 90 menit. Data dalam penelitian ini diperoleh dari hasil tes tertulis pada akhir siklus pertama dan kedua serta hasil observasi pada setiap pertemuan oleh satu orang guru sebagai observer. Hasil penelitian ini menunjukkan bahwa terjadi peningkatan hasil belajar siswa pada siklus I dengan persentase ketuntasan sebesar 62,5% dan tidak tuntas sebesar 37,5%. Pada siklus kedua terjadi peningkatan hasil belajar siswa dengan persentase ketuntasan sebesar 91,66% dan persentase tidak tuntas sebesar 8,34%.  Aktivitas siswa juga mengalami peningkatan dari kategori aktif menjadi sangat aktif dengan rata-rata persentase keaktifan adalah 90,63%.  Hal ini membuktikan bahwa kegiatan pembelajaran menggunakan model explicit instruction dapat meningkatkan hasil belajar siswa dan mampu mendorong keaktifan siswa dalam proses pembelajaran. Dengan demikian penelitian ini menyimpulkan bawah penerapan model pembelajaran explicit instruction pada siswa X IPA 2 materi stoikiometri terbukti dapat meningkatkan hasil dan aktivitas belajar siswa.